The information in term structure interest rate spreads: the Irish case - Hurley, Margaret (Economic & Social Studies, 1990)
The study of the term structure of interest rates looks at how the yields on bonds vary with time to maturity. Yield curves can be upward sloping, humped or downward sloping and their shape is often taken to be an indication of whether interest rates and/or inflation rates are expected to rise or fall. This forecasting potential results from the decision-making process of profitseeking investors, which must involve the formation of expectations on future inflation and interest rates. Theory suggests that, if markets are efficient, it should be possible to extract the aggregate of these expectations of inflation and interest rates from observable term structure data. I t then only requires that expectations be rational for forecasting power to be deduced.
Keywords: Interest rates; Inflation; Ireland; Term structures